2018
DOI: 10.1371/journal.pone.0206358
|View full text |Cite|
|
Sign up to set email alerts
|

Hormonal contraceptive use and risk of pancreatic cancer—A cohort study among premenopausal women

Abstract: ImportanceThe association between the use of hormonal contraceptive and pancreatic cancer among premenopausal women has until now been unclear. This is the first study to investigate the risk of pancreatic cancer in pre-menopausal women.ObjectiveTo determine whether hormonal contraception increases the risk of developing pancreatic cancer in pre-menopausal women.DesignA nationwide prospective cohort study followed all women in Denmark in the age range of 15–49 years without previous cancer or venous thrombosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…A previous meta-analysis by Tang et al and the study by Butt et al based on all premenopausal women in Denmark found no effect of OC use on pancreatic cancer incidence, which was supported by a recent prospective cohort study. 12 , 26 , 27 As our study sample consisted of women with a mean age of approximately 50 years at baseline, our study is not suitable for assessing the effects of current OC use in relation to pancreatic cancer incidence, as the prevalence of current use was very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous meta-analysis by Tang et al and the study by Butt et al based on all premenopausal women in Denmark found no effect of OC use on pancreatic cancer incidence, which was supported by a recent prospective cohort study. 12 , 26 , 27 As our study sample consisted of women with a mean age of approximately 50 years at baseline, our study is not suitable for assessing the effects of current OC use in relation to pancreatic cancer incidence, as the prevalence of current use was very low.…”
Section: Discussionmentioning
confidence: 99%
“… 26 More recent prospective studies have mainly supported the finding of no association with use of OCs. 12 , 27 For MHT use, controversies exist, and inverse relationships between MHT use and pancreatic cancer risk have recently been reported. 8 , 19 , 22 Furthermore, one study has identified increased risk with increasing age at menarche.…”
Section: Introductionmentioning
confidence: 99%
“…Still, tamoxifen, which is currently recognized as a GPER agonist [16], is broadly used as first-line treatment for human breast cancer. While concerns could be raised that the proliferative estrogenic effects in the pancreas might affect the exocrine pancreas as well, the limited clinical and epidemiological information accrued thus far does not support this possibility [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In einer aktuellen Metaanalyse und in der großen dänischen Kohortenstudie wurden keine Zusammenhänge zwischen hormoneller Kontrazeption und dem Risiko für ein Pankreaskarzinom gefunden [11,33]. In der finnischen Levonorgestrel-IUP-Kohortenstudie war das Pankreaskarzinomrisiko bei Anwenderinnen deutlich reduziert (SIR 0,5; 95 %-KI 0,28-0,81) [6].…”
Section: Pankreaskarzinomeunclassified
“…In der finnischen Levonorgestrel-IUP-Kohortenstudie war das Pankreaskarzinomrisiko bei Anwenderinnen deutlich reduziert (SIR 0,5; 95 %-KI 0,28-0,81) [6]. Dies mag z. T. darauf zurückzuführen sein, dass die Anwenderinnen von Levonorgestrel-IUP sich in den nicht erfassten Confoundern (Rauchen, Alkohol, Adipositas) von der Vergleichsgruppe (Normalbevölkerung) unterschieden und für diese Parameter in der finnischen im Gegensatz zur dänischen Studie nicht korrigiert wurde [6,11].…”
Section: Pankreaskarzinomeunclassified